(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article scientifically analyzes and discusses information about the work done on socio-economic issues in the neighborhoods of Shahrisabz during the years of independence, as well as measures aimed at ensuring their implementation.